Movimentos feministas, minorias ativas: percurso de um coletivo de estudantes brasileiras do ensino médio integrado - Castro, Vanessa Soares de (2019)
This thesis’ goal is to study organization and mobilization processes of a feminist collective called Ovelhas Negras (Black Sheep), which was created by high school female students, whose course is integrated with technical courses at a Brazilian Federal Education Institution (IFE, is the acronym in Portuguese), located in the state of Rio Grande do Sul, Brazil. Research is part of the umbrella project Vidas precárias no cibermundo — Estudos sobre violências, poder e interseccionalidade nos sistemas hierárquicos (Precarious Lives in Cyberworld — Studies on Violence, Power and Intersectionality in Hierarchical Systems). The overall goal is to understand the interconnections between the meanings of feminism for the Black Sheep Movement, and how the collective works to promote changes in everyday school life, by identifying: (a) representations that the collective has developed about feminisms and about its own feminist activity in the process of constructing its practices; (b) relational dynamics developed by the collective with many social actors, as an active minority in their territory. Specific goals are: to identify the participating collective transformation and influence potentials, from its dynamics and set of actions, aiming at how it keeps moving; to get to know the knowledge produced by the collective, by regarding the foundations of its activist project and the ethical dimension of its proposal; to identify what relations are established between the collective and third parties, both antagonists and allies, by regarding limits and possibilities of its political action in territory. The development of this research was based on Social Representation Theory, and also on the Theory of Active Minorities, Feminist Studies and Gender Studies. Along with theoretical perspectives and the goals proposed, my goal is to outline research qualitatively, from the participation research, by emphasizing the use of techniques that engage participants on the research—in this case, the students that take part in the collective. At the same time, I have worked to give special attention to observing real contexts where interactions and collective practices occur. In order to produce empirical information, a field diary was written that reports my participation in collective meetings and activities, along with other moments that are relevant for research. Also, a round of conversation was carried out, to systematize experiences with participants. The analysis of material was made by building a spiral on the collective’s historical and cultural contextualization. Analysis of material allowed for the discussion of how the collective was originated, its forms of organization, how new members and supporters join the group, the knowledge that is produced in it—especially in relation to how feminism is understood and what it means to be feminist, and how the collective deals with relations of otherness. From those points, the potential of mobilizing youngsters in school space are regarded, specially in autonomous ways, working not only as education spaces for more critical and active social actors, but also to cause changes in school space itself.